2001
DOI: 10.1521/pedi.15.1.94.18644
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Of Community-Oriented and Hospital-Oriented Care for Discharged Psychiatric Patients: Influence of Personality Disorder on Police Contacts

Abstract: An important forensic psychiatric measure, contacts with police, was compared in a randomized, controlled trial of 155 patients with severe mental illness with a previous admission within the past two years. The patients, who also had their personality status addressed formally before randomization, were allocated to community multidisciplinary teams or to hospital-based care programs after discharge from in-patient care and were followed up for one year. A total of 138 patients (89%) had at least one post-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Some other studies (e.g. Dean et al, 2006;Dolan & Davies, 2006;Gandhi et al, 2001) are also in keeping with this conclusion. It may also be relevant that most assessments for personality disorder, particularly in the United States, depend on cooperative and insightful patients, and in schizophrenia this degree of cooperation and awareness is missing.…”
Section: Discussionsupporting
confidence: 82%
“…Some other studies (e.g. Dean et al, 2006;Dolan & Davies, 2006;Gandhi et al, 2001) are also in keeping with this conclusion. It may also be relevant that most assessments for personality disorder, particularly in the United States, depend on cooperative and insightful patients, and in schizophrenia this degree of cooperation and awareness is missing.…”
Section: Discussionsupporting
confidence: 82%
“…FACT consumers were more likely to be diagnosed with antisocial personality disorders and this is particularly important for FACT teams to know in light of evidence that schizophrenia and antisocial personality disorder combine to create a number of challenges, such as increased homelessness, greater psychosis, higher rates of police contact and persistent criminality, increased violent and suicidal behaviors, and increased substance abuse (Gandhi, Tyrer, Evans, McGee, Lamont, & Harrison-Read, 2001; Hodgins & Cote, 1993; Moran, Walsh, Tyrer, Burns, Creed, & Fahy, 2003a; Moran, Walsh, Tyrer, Burns, Creed, & Fahy, 2003b; Moran &…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that people with personality disorders managed under an assertive community approach are more likely to show antisocial behaviour than are those managed under a more hospital-oriented policy (Gandhi et al, 2001). People with personality disorders have fewer attachment and support figures in the community than do others (Tyrer et al, 1994), and few community teams can provide the level of support and treatment needed when function begins to disintegrate.…”
Section: Box 4 Engagement and Maintenance In Treatmentmentioning
confidence: 99%